CORRELATION BETWEEN METHODS OF QUANTIFYING OF TRAINING LOAD IN A SESSION OF COMBATS OF JIU-JITSU (Fiep Bulletin - online, 2011)
The purpose of this study was to analyze the correlation between different methods of quantifying of training load in a session of combats of jiu-jitsu. Five male athletes from jiu-jitsu, aged between 18-27 years and with more than two years of practice, participated in this study. The participants underwent anthropometric measurements, medical history, assessment of maximal heart rate and three combats of jiu-jitsu with lasted of five minutes each and with equal time recovery between them. The participants signed the consent agreement agreeing in participate in this research. Heart rate was continuously monitored by cardiofrequency (Polar S610i) during the session of combat and after 30 min the participants indicated the perceived exertion of the session in a specific scale. From this, the training load was calculated by the methods based on heart rate and perceived exertion of the session (PES), as Edwards (1993) and Foster et al., (1996), respectively. The correlation between the different methods of quantifying training load was analyzed by the Pearson correlation coefficient. It was adopted p 0.05; r=0.85) between methods of quantifying training load. The low number of participants and not application of more reliable physiological parameter to validate the PES in sessions of combats of jiu-jitsu are the main limitations of this research. In this sense, it is recommended that other research can be developed with the intent to have more knowledge about the limitations and potential of the use of PES as means of quantifying training load internal by coaches and physical trainers of jiu-jitsu fighters as well as the others martial arts.